2018
DOI: 10.1109/jlt.2018.2852061
|View full text |Cite
|
Sign up to set email alerts
|

Noise Investigation of a Dual-Frequency VECSEL for Application to Cesium Clocks

Abstract: We theoretically and experimentally study the noise of a class-A dual-frequency vertical external cavity surface emitting laser operating at Cesium clock wavelength. The intensity noises of the two orthogonally polarized modes and the phase noise of their beatnote are investigated. The intensity noises of the two modes and their correlations are well predicted by a theory based on coupled rate equations. The phase noise of the beatnote is well described by considering both thermal effects and the effect of pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…This confirms the expectation that the full in-phase pumping combined with a very low non-linear coupling constant C are favorable conditions for the in-phase noise to dominate. Indeed, such a domination of the in-phase mechanism was predicted in [6], which states that decreasing the coupling between the two modes favors in-phase noise with respect to anti-phase noise. The dramatic anti-phase noise reduction corroborates the fact that the gain competition between the two modes is well inhibited.…”
Section: Device Implementation For Fully-correlated Pumpingmentioning
confidence: 85%
See 3 more Smart Citations
“…This confirms the expectation that the full in-phase pumping combined with a very low non-linear coupling constant C are favorable conditions for the in-phase noise to dominate. Indeed, such a domination of the in-phase mechanism was predicted in [6], which states that decreasing the coupling between the two modes favors in-phase noise with respect to anti-phase noise. The dramatic anti-phase noise reduction corroborates the fact that the gain competition between the two modes is well inhibited.…”
Section: Device Implementation For Fully-correlated Pumpingmentioning
confidence: 85%
“…The beat note spectra are plotted versus the frequency offset from the carrier. The wider spectrum (in blue) corresponds to the single pump spot scheme reported in [6] whereas the other one (in orange) corresponds to the two fully in-phase correlated pumps. Figure 6 plots the power spectral density of phase fluctuations of the VECSEL beat note.…”
Section: Phase Noise Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, DF-laser beat-note stabilization has already been implemented in DBR fiber lasers with optical feedback [9] or optical phase-locked loops (OPLL) [10]. However, noise investigations in free running DF-VECSELs operating at cesium clock wavelength have shown that the intensity noise and the beat-note phase noise of the free running lasers mainly originate from the intensity noise of the pump laser [11]. The way this pump noise is transferred to the intensity and beat-note phase noises of the DF-VECSEL depends mainly on i) the laser dynamical behavior through the nonlinear coupling constant between the two laser modes and ii) the correlations between the noises of the pump power seen by the two modes.…”
Section: Introductionmentioning
confidence: 99%